Facilitating adherence to physical activity: exercise professionals' experiences of the National Exercise Referral Scheme in Wales. a qualitative study - Moore Graham F; Moore Laurence; Murphy Simon (BMC, 2011)
Abstract Background Although implementers' experiences of exercise referral schemes (ERS) may provide valuable insights into how their reach and effectiveness might be improved, most qualitative research has included only views of patients. This paper explores exercise professionals' experiences of engaging diverse clinical populations in an ERS, and emergence of local practices to support uptake and adherence in the National Exercise Referral Scheme (NERS) in Wales. Methods Thirty-eight exercise professionals involved in the delivery of NERS in 12 local health board (LHB) areas in Wales took part in a semi-structured telephone interview. Thematic analysis was conducted. Results Professionals' accounts offered insights into how perceived needs and responses to NERS varied by patient characteristics. Adherence was described as more likely where the patient sought referral from a health professional rather than being advised to attend. Hence, professionals sometimes described a need for the referral process to identify patients for whom change was already internally motivated. In addition, mental health patients were seen as facing additional barriers, such as increased anxieties about the exercise environment. Professionals described their role as involving helping patients to overcome anxieties about the exercise environment, whilst providing education and interpersonal support to assist patients' confidence and motivation. However, some concerns were raised regarding the levels of support that the professional should offer whilst avoiding dependence. Patient-only group activities were described as supporting adherence by creating an empathic environment, social support and modelling. Furthermore, effectively fostering social support networks was identified as a key mechanism for reducing dependence and maintaining changes in the longer term. Conclusions Whether ERS should identify motivated patients, or incorporate activities to support internalisation of motivation amongst less motivated patients deserves attention. As well as providing the knowledge to advise patients on how to exercise safely given their conditions, professionals' training should focus on providing the skills to meet the interpersonal support needs of patients, particularly where ERS are used as a means of improving mental health outcomes. The effectiveness of emerging activities, such as post-scheme maintenance classes, in fostering long-term social networks supportive of physical activity deserve attention. Trial registration Current Controlled Trials: ISRCTN47680448